Analysis on characteristics of coal-rock gas dynamic disasters based on stress grading action mechanism - Wei ZHAO; Zexin LI; Dan ZHAO; Aitao ZHOU; Jie ZANG; Xiongfei PEI (Meikuang Anquan)
With the gradual depletion of shallow coal resources, coal mining in China gradually extends to the deep. With the increase of buried depth, the stress state will change and the type of stress field will also change, which makes the internal stress distribution of coal and rock show a hierarchical grading trend. This stress classification results in the difference of physical and mechanical characteristics of coal and rock as well as the environment of gas occurrence and migration, thus affecting the occurrence characteristics of coal and rock gas dynamic disasters. In order to analyze the effect of stress grading on coal gas dynamic disaster, the mechanism of stress grading is reviewed. The results show that the stress state changes under the effect of stress gradation, which leads to the different development degree and failure state of tectonic coal, and the tectonic coal seam with higher failure degree tends to develop towards the state of hydrostatic stress. When the pores in coal are at the critical depth, the pores and micropores are more developed, the pore specific surface area and pore volume are larger, and the crack direction also changes from horizontal to vertical, which affects the permeability of coal seam and the migration path of gas. The gas content increases first and then decreases with the increase of burial depth. With the deepening of depth and the change of lateral pressure coefficient, the shape of the outburst cavity changes from semi-elliptical to butterfly shape. The different stress states in shallow and deep areas also change the dynamic disaster form of coal, rock and gas. Based on the above research, this paper puts forward the idea of disaster zone management that the shallow part is dominated by gas extraction, and the deep part is coordinated by unloading energy dissipation and gas extraction. In the future, it is necessary to think about how to improve and practice the pressure-relief energy dissipation medium modification collaborative technology system to effectively reduce or avoid coal, rock and gas dynamic disasters caused by stress changes, so as to cope with the challenges brought by deep coal seam mining.